STUDI KOMPARATIF TERAPI RENDAM KAKI AIR JAHE MERAH (ZINGIBER OFFICINALE VAR RUBRUM) HANGAT DAN TERAPI RENDAM AIR HANGAT TANPA JAHE MERAH TERHADAP PENURUNAN TEKANAN DARAH ROT MAP PADA IBU PREEKLAMSIA - Qurrotu aini; Merlyna Suryaningsih; Eny Susanti; Kurnia Chotimul Qur´aini (NHM PRESS, 2023)
Preeclampsia is a symptoms in pregnant woman characterized by hypertension, positive proteinuria, and edema. Based on the results of the preliminary study 32.6% of preeclampsia patients were found at Syarifah Ambami Rato Ebu, hospital. This study aims to determine the effect of foot soaking with warm ginger to reduce blood pressure in preeclampsia women at Syarifah Ambami Rato Ebu,general hospital. The research design used a Quasy Experiment design. The population of 33 patients with 8 respondents in the ntervention group and 8 respondents in the control group using the random sampling technique. The independent variable were foot soak with warm ginger therapy and the dependent variable was reducing blood pressure in preeclampsia women, with ROT and MAP sub-variables. The instruments used are observation sheets for blood pressure measuring and SOP for foot soaking with warm ginger. Statistical test using independent t-test with (a=0.05). The results showed that based on the independent t-test statistical test on reducing blood pressure ROT with test results (p=0.002) < (a=0.05), while the independent t-test statistical test on reducing MAP blood preesure with test results (p=0.019) < (a=0.05). So it concluded that there were differences in ROT and MAP blood pressure values in preeclampsia patients at Syarifah Ambami Rato Ebu,general hospital. It is recommended that preeclampsia patients do foot soak with warm ginger therapy which is very easy to apply at home independently to reducing blood pressure during the 2nd and 3rd trimesters of pregnancy